Engagement in the city how arts and culture impact development in urban areas - Hersey, Leigh Nanney 1971-; Bobick, Bryna 1974- (Lexington Books, 2021)
Engagement in the City: How Arts and Culture Impact Development in Urban Areas explores how the arts contribute to cultural and economic development, physical and mental health, education, and social capital. The book can be helpful for scholars and community leaders interested in facilitating arts-based initiatives to improve their communities
Keywords: Gesundheit; Bedeutung; Bildung; Stadtviertel; Politik; Kultur; Kunst; Nachbarschaft; USA; Sociology, Urban / United States; Art and society / United States; City planning / Social aspects / United States; Community development / United States; Art and society; City planning / Social aspects; Community development; Sociology, Urban; Aufsatzsammlung